2016
DOI: 10.1126/science.aah4993
|View full text |Cite
|
Sign up to set email alerts
|

The genomic landscape of rapid repeated evolutionary adaptation to toxic pollution in wild fish

Abstract: Atlantic killifish populations have rapidly adapted to normally lethal levels of pollution in four urban estuaries. Through analysis of 384 whole killifish genome sequences and comparative transcriptomics in four pairs of sensitive and tolerant populations, we identify the aryl hydrocarbon receptor-based signaling pathway as a shared target of selection. This suggests evolutionary constraint on adaptive solutions to complex toxicant mixtures at each site. However, distinct molecular variants apparently contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
438
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 379 publications
(469 citation statements)
references
References 43 publications
23
438
8
Order By: Relevance
“…For example, theoretical and analytical studies have developed and incorporated evolutionary techniques for ecotoxicology (e.g., Bélanger‐Deschênes et al., 2013; Klerks, Xie, & Levinton, 2011) while conceptual studies have developed frameworks for integrating evolution and ecotoxicology (e.g., Leung et al., 2017). Empirical studies have increasingly been detecting evolutionary responses in diverse environmental contexts, for example, in response to mining effluents and industrial pollutants (Bougas et al., 2016; Chen et al., 2015; García‐Balboa et al., 2013; Laporte et al., 2016; Reid et al., 2016). Studies are also beginning to show that adaptation to toxicants can evolve at a cost, for example, in the form of increased sensitivity to oxidative stress following adaptation to PCBs (Harbeitner, Hahn, & Timme‐Laragy, 2013).…”
Section: Evolutionary Toxicology—building a Foundation For Toxicologymentioning
confidence: 99%
“…For example, theoretical and analytical studies have developed and incorporated evolutionary techniques for ecotoxicology (e.g., Bélanger‐Deschênes et al., 2013; Klerks, Xie, & Levinton, 2011) while conceptual studies have developed frameworks for integrating evolution and ecotoxicology (e.g., Leung et al., 2017). Empirical studies have increasingly been detecting evolutionary responses in diverse environmental contexts, for example, in response to mining effluents and industrial pollutants (Bougas et al., 2016; Chen et al., 2015; García‐Balboa et al., 2013; Laporte et al., 2016; Reid et al., 2016). Studies are also beginning to show that adaptation to toxicants can evolve at a cost, for example, in the form of increased sensitivity to oxidative stress following adaptation to PCBs (Harbeitner, Hahn, & Timme‐Laragy, 2013).…”
Section: Evolutionary Toxicology—building a Foundation For Toxicologymentioning
confidence: 99%
“…Population resequencing allows for full comparisons between populations at each nucleotide, which gives it enormous power for analyzing population structure, demography, divergence, and identifying specific sequences associated with resistant phenotypes. Such projects are currently underway in both Fundulus heteroclitus (Reid et al., 2016) and F. grandis , and represent one of the most in‐depth approaches in evolutionary toxicology. The power of this approach is exemplified in a recent study of aging in turquoise killifish, Nothobranchius furzeri , which identified the specific genes responsible for an incredibly rapid generation turnover in this fish (Valenzano et al., 2015).…”
Section: Evolutionary and Population Genomicsmentioning
confidence: 99%
“…Studies suggest that in order to be able to predict many population‐wide statistics with power, at least 20–30 individuals per population need to be sequenced in order to reliably measure heterozygosity and to test for Hardy–Weinberg equilibrium at all loci (Luikart et al., 2003). On the other hand, the specific genetic changes of very recent selective sweeps are unavoidably difficult to pinpoint even with full‐genome population resequencing (Reid et al., 2016). Such sweeps result in portions of the genome to appear to be under selection because of genetic hitchhiking surrounding the causative region.…”
Section: Evolutionary and Population Genomicsmentioning
confidence: 99%
See 2 more Smart Citations